2018
DOI: 10.1016/j.jtemb.2017.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Early pregnancy maternal trace mineral status and the association with adverse pregnancy outcome in a cohort of Australian women

Abstract: Maternal micronutrient deficiencies in pregnancy can have profound effects on fetal development and pregnancy outcome. Plasma trace minerals including copper, zinc, selenium and iron have been shown to be extremely important in supporting reproduction. We sought to determine whether there is an association between maternal trace mineral status in early pregnancy and pregnancy complications using a prospective cohort study of 1065 pregnant Australian women who were recruited as part of the Screening for Pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 44 publications
9
67
2
1
Order By: Relevance
“…A number of studies have reported average plasma selenium concentrations far below this value (Stoffaneller & Morse, ), including within cohorts of pregnant women (Wilson et al . ). At concentrations below this level, selenoproteins that are essential for pregnancy health, may function at suboptimal levels, leading to impaired fetal growth, which may, in turn, program disease in offspring.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A number of studies have reported average plasma selenium concentrations far below this value (Stoffaneller & Morse, ), including within cohorts of pregnant women (Wilson et al . ). At concentrations below this level, selenoproteins that are essential for pregnancy health, may function at suboptimal levels, leading to impaired fetal growth, which may, in turn, program disease in offspring.…”
Section: Introductionmentioning
confidence: 97%
“…Research has suggested that, to maximize activity of the essential selenoprotein anti-oxidant glutathione peroxidase (GPX), plasma selenium concentrations in humans should be ß100 µg L -1 (Stoffaneller & Morse, 2015). A number of studies have reported average plasma selenium concentrations far below this value (Stoffaneller & Morse, 2015), including within cohorts of pregnant women (Wilson et al 2018). At concentrations below this level, selenoproteins that are essential for pregnancy health, may function at suboptimal levels, leading to impaired fetal growth, which may, in turn, program disease in offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological data indicate that adverse pregnancy outcomes and pregnancy complications, including preterm births, preeclampsia (PE), gestational diabetes, and fetal growth restriction (IUGR), occur in total in up to 25% of first pregnancies [1] and these pregnancy results are an important element of public health. They are associated with an increase in maternal and fetal morbidity and/or mortality [2][3][4][5][6][7][8][9][10] and they may lead to long-term diseases of both the mother and the child, increasing the risk of cardiovascular diseases, obesity, diabetes, and even some cancers, as well as neurodevelopmental disorders in the offspring [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact mechanisms linking environmental factors to thyroid autoimmunity are not as yet fully understood, there is increasing evidence that the following environmental factors are involved in development of autoimmune diseases: environmental pollution (e.g., organochlorines and pesticides), nutrients with iodine, Se, iron, zinc, vitamin B12, and D, irradiation, drugs (interferon α and γ, TNF-α), smoking, obesity, socioeconomic status, infections, stress, lifestyle, and pregnancy [30]. Recently published data from Australia showed that lower plasma copper measured at pregnancy week 15, even though adjusted to Se and zinc status, had decreased the risk of any pregnancy complications [31]. The authors concluded that further research to determine the role of trace elements in early pregnancy should specifically focus on their interactions in supporting fetal development and pregnancy outcome.…”
Section: Se Sources and Daily Requirement In Pregnancymentioning
confidence: 99%